eIF3b-driven autophagy and Wnt/β-catenin crosstalk: a novel regulatory axis in adriamycin resistance of breast cancer - Li, Yanhui; Chen, Shurao; Zhao, Zihui; Yuan, Zhikun; Yuan, Dehan (Oncology Reviews, 2025)
Adriamycin (ADM) resistance remains a major clinical obstacle in breast cancer chemotherapy, driven by complex mechanisms including enhanced drug efflux, apoptosis inhibition, and protective autophagy. This review explores a novel regulatory axis centered on eukaryotic initiation factor 3b (eIF3b) and its interplay with autophagy and the Wnt/β-catenin signaling pathway in ADM resistance. Emerging evidence indicates that eIF3b, a crucial subunit of the translation initiation complex, is significantly overexpressed in ADM-resistant breast cancer tissues and cell lines. Crucially, our preliminary experimental findings demonstrate that downregulation of eIF3b suppresses autophagy and concurrently sensitizes resistant breast cancer cells to ADM. While protective autophagy is a well-established resistance mechanism, and the Wnt/β-catenin pathway significantly contributes to multidrug resistance, the specific role of eIF3b and its potential crosstalk with these pathways in ADM resistance is poorly understood. This review synthesizes current knowledge, highlighting the strong evidence suggesting eIF3b acts as an upstream regulator of autophagy to promote ADM resistance. Furthermore, it discusses the potential involvement of the Wnt/β-catenin pathway in this regulatory network, and proposes several hypothetical models of interaction among eIF3b, autophagy, and Wnt/β-catenin signaling. Elucidating the precise molecular mechanisms by which eIF3b drives autophagy and potentially interacts with Wnt/β-catenin holds significant promise for identifying novel therapeutic targets to overcome ADM resistance and improve breast cancer treatment outcomes. Ultimately, targeting the eIF3b-autophagy-Wnt/β-catenin axis could provide a innovative translational strategy to reverse chemoresistance in breast cancer patients.